Черный пиар: [роман] / Ф. Е. Незнанский - Незнанский Фридрих Евсеевич (Господин адвокат, 2003)
Экземпляры: ф.1 (20181113) / Инвентарный номер: 58917 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Н 44 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44